The Addition of Sirolimus to GVHD Prophylaxis After Allogeneic Hematopoietic Stem Cell Transplantation: A Meta-Analysis of Efficacy and Safety - Chen, Xiaoli; Sun, Hengrui; Cassady, Kaniel; Yang, Shijie; Chen, Ting; Wang, Li; Yan, Hongju; Zhang, Xi; Feng, Yimei (Frontiers in Oncology, 2021)
Objective: To evaluate the safety and efficacy of sirolimus (SRL) in the prevention of graft-versus-host disease (GVHD) in recipients following allogeneic hematopoietic stem cell transplantation (allo-HSCT). Methods: Randomized controlled trials (RCTs) evaluating the safety and efficacy of SRL-based prophylaxis regimens in patients receiving allo-HSCT were obtained from PubMed, Embase, and the Cochrane database. Following specific inclusion and exclusion criteria, studies were selected and screened by two independent reviewers who subsequently extracted study data. The Cochrane risk bias evaluation tool was used for quality evaluation, and RevMan5.3 software was used for statistical analysis comparing the effects of SRL-based and non–SRL-based regimens on acute GVHD, chronic GVHD, overall survival (OS), relapse rate, non-relapse mortality (NRM), thrombotic microangiopathy (TMA) and veno-occlusive disease (VOD). Results: Seven studies were included in this meta-analysis, with a total sample size of 1673 cases, including 778 cases of patients receiving SRL-based regimens and 895 cases in which patients received non-SRL-based regimens. Our data revealed that SRL containing prophylaxis can effectively reduce the incidence of grade II-IV acute GVHD (RR=0.75, 95%CI: 0.68～0.82, P<0.0001) . SRL-based prophylaxis was not associated with an improvement of grade III-IV acute GVHD (RR=0.78, 95%CI: 0.59～1.03, P=0.08), chronic GVHD (P=0.89), OS (P=0.98) and Relapse rate (P=0.16). Despite its immunosuppressant effects, SRL-based regimens did not increase bacterial (P=0.68), fungal (P=0.70) or CMV (P=0.10) infections. However, patients receiving SRL-based regimens had increased TMA (P<0.00001) and VOD (P<0.00001). Conclusions: This meta-analysis indicates that addition of sirolimus is an effective alternative prophylaxis strategy for II-IV aGVHD, but may cause endothelial cell injury and result in secondary TMA or VOD events.